Development and Prototyping of an Accurate and Cost-efficient Digital Sampling Multi-Meter Using Instantaneous Power Calculation Algorithm (Diyala Journal of Engineering Sciences, 2025)
The parameters of an electrical power system have wide variations during the operation of electrical devices; these changes are required to be measured using an accurate meter. A cost-effective Digital Sampling Multi-meter (DSMM) using a microcontroller and two sensors was proposed to overcome the complexity of traditional power meters. Voltage and current signals from sensors were discretely time-sampled and then analysed based on the Instantaneous Power Calculation Algorithm (IPCA) using an Arduino to measure six of the electrical quantities. It Root Mean Square (RMS) terminal voltage and load current, real, reactive, and apparent power, and finally Power Factor (PF), then these were displayed on both the LCD and the PC serial monitor. Also, the instantaneous waveforms of the voltage, current, and power are easily analysed and plotted with any type of load. The IPCA algorithm was adopted because of its real-time measurement, high accuracy, ease of implementation, and low cost. Measurements are performed for linear loads (resistive, inductive, and capacitive) and non-linear loads (rectifier circuits). The proposed meter's accuracy was found to have acceptable relative percentage errors for most measured parameters, especially at linear loads (maximum relative error for Vrms 0.7% at inductive load, 5% for Irms at capacitive load, and 5% for PF at capacitive load), calculated based on the FLUKE Power Quality Meter, which was considered a high-quality measurement instrument.